Pendidikan Kesehatan Gigi dan Mulut kepada Komunitas All New Rush Terios Indonesia - Perwira Lubis, Novo; Priandini, Dewi; Livia Kurniawan, Florencia; Hanin, Isya; Wulanasari, Selviana; Avila Johannes, Gerald; Meliani (JURNAL ABDIMAS KESEHATAN TERPADU, 2023)
Oral health contributes to individual's physical, mental, and social well-being and significantly impacts their quality of life. Preventing oral diseases and promoting oral health contribute to overall well-being, enhancing their quality of life. Community-level or population-based prevention is the most cost-effective approach with the greatest impact on communities or populations, whether in schools or neighborhoods. Oral health education aims to enhance overall knowledge, potentially leading to the adoption of beneficial oral health behaviors. The provision of oral health education is expected to elevate public knowledge and awareness, enabling individuals to maintain or enhance their oral health and thus improve their quality of life. Offline activities involving oral health education were conducted through presentations on May 7th, 2023, at Giova’s Garden, Bogor. Various topics, including dental radiographic examination, primary management of dental trauma, dental prosthesis rehabilitation, oral health in children, and tips for maintaining oral health while driving, were presented to enhance participants' knowledge about oral health. The community engagement activity proceeded smoothly. Similar activities are anticipated to be carried out again with pre-test and post-test assessments to evaluate the effectiveness of the education provided.